Malignant monotypic epithelioid angiomyolipoma of the kidney. - Warakaulle, DR; Phillips, R; Turner, G; Davies, D; Protheroe, A (2004)
In summary, this case highlights the importance of considering epithelioid AML in the differential diagnosis of renal tumours, particularly in patients with associated conventional AMLs and/or other evidence of TS. In a patient with TS, a non-cystic renal mass is most likely to be an AML, even in the absence of radiological detection of fat due to haemorrhage or minimal fat content in an AML composed predominantly of smooth muscle. It may, however, represent a RCC or potentially a malignant epithelioid AML. Definitive demonstration of the benign nature of this patient's liver lesions was crucial for further management. © 2004 The Royal College of Radiologist. Published by Elsevier Ltd. All rights reserved.